2021
DOI: 10.1017/s1041610221000569
|View full text |Cite
|
Sign up to set email alerts
|

Management of delirium in older adults: challenges and opportunities

Abstract: Management of delirium in older adults: challenges and opportunitiesDelirium is a vexing clinical problem in hospitalized older adults. Despite the established association between delirium and death, morbidity, institutionalization, and patient distress (Siddiqi et al., 2006), few high-quality studies examining the management of delirium in older adults exist. Delirium management strategies can be broadly divided into those addressing prevention or treatment, as well as pharmacological and non-pharmacological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The authors conclude that there is no high-quality evidence supporting the use of anticonvulsants in preventing or treating delirium in hospitalized older adults. Fortunately, several initiatives are currently underway to standardize delirium research (Bingham and Flint, 2022). Some multicomponent prevention studies have suggested useful strategies for delirium management.…”
mentioning
confidence: 99%
“…The authors conclude that there is no high-quality evidence supporting the use of anticonvulsants in preventing or treating delirium in hospitalized older adults. Fortunately, several initiatives are currently underway to standardize delirium research (Bingham and Flint, 2022). Some multicomponent prevention studies have suggested useful strategies for delirium management.…”
mentioning
confidence: 99%